IMPLEMENTASI MINGLE DI LAFAYETTE BOUTIQUE HOTEL YOGYAKARTA - Ajie Wicaksono; Okta Nafisa Mardiani (STIE Pariwisata API Yogyakarta, 2020)
This study aims: (1) to determine the role of staf salesin the implementation of the mingle at Lafayette Boutique Hotel Yogyakarta, and (2) to determine the description of the implementation of the mingle at Lafayette Boutique Hotel Yogyakarta. This research uses descriptive qualitative method, by collecting data through observation, interviews, documentation. Data retrieval of data was carried out in December 2018-February 2019. Data analysis used Miles and Huberman which included data reduction, data presentation and drawing conclusions / verification. The results showed that the mingle activity can be used as a direct evaluation of guests as a measure of the level of guest satisfaction related to the income that the hotel will receive as income. In mingle activities, staf saleshave a role in communicating with guests to build relationships, inform Direct Booking guests of Online Travel Agents, report to All Departments, and Maintain operations. Lafayette Boutique Hotel Yogyakarta has implemented a scheduled and structured mingle by adjusting the number of staff that has been approved by the Director of Sales, which is every day at the restaurant at breakfast time, starting at 09.00 to 10:00 am includes 3 activities namely recording the guest database as a marketing system, offering Experience Of French, and retarget guests.